Chloroplast DNA footprints of postglacial recolonization by oaks - Petit, Rémy J. (National Academy of Sciences, 1997)
Recolonization of Europe by forest tree species after the last glaciation is well documented in the fossil pollen record. This spread may have been achieved at low densities by rare events of long-distance dispersal, rather than by a compact wave of advance, generating a patchy genetic structure through founder effects. In long-lived oak species, this structure could still be discernible by using maternally transmitted genetic markers. To test this hypothesis, a fine-scale study of chloroplast DNA (cpDNA) variability of two sympatric oak species was carried out in western France. The distributions of six cpDNA length variants were analyzed at 188 localities over a 200 × 300 km area. A cpDNA map was obtained by applying geostatistics methods to the complete data set. Patches of several hundred square kilometers exist which are virtually fixed for a single haplotype for both oak species. This local systematic interspecific sharing of the maternal genome strongly suggests that long-distance seed dispersal events followed by interspecific exchanges were involved at the time of colonization, about 10,000 years ago.